Temporary General Equilibrium Theory - Grandmont, Jean Michel (Econometrica, 1977)
This paper surveys some recent studies of economies where trading takes place sequentially over time, and where each agent makes decisions at every date in the light of his expectations about his future environment, which are functions of his information on the present and past states of the economy. The paper reviews particularly the issues raised by arbitrage in capital markets, by the consideration of money and banking activities, and by the introduction of production in temporary competitive equilibrium models. A thorough investigation of the logic of temporary equilibrium models with quantity rationing is also offered, as well as a quick review of the study of stochastic processes of temporary equilibria.